Respiratory problems in children with esophageal atresia and tracheoesophageal fistula - Federica Porcaro; Laura Valfré; Lelia Rotondi Aufiero; Luigi Dall'Oglio; Paola De Angelis; Alberto Villani; Pietro Bagolan; Sergio Bottero; Renato Cutrera (BMC, 2017)
Abstract Background Children with congenital esophageal atresia (EA) and tracheoesophageal fistula (TEF) have chronic respiratory symptoms including recurrent pneumonia, wheezing and persistent cough. The aim of this study is to describe the clinical findings of a large group of children with EA and TEF surgically corrected and the instrumental investigation to which they have undergone in order to better understand the patient's needs and harmonize the care. Methods A retrospective data collection was performed on 105 children with EA and TEF followed at Department of Pediatric Medicine of Bambino Gesù Children's Hospital (Rome, Italy) between 2010 and 2015. Results 69/105 (66%) children reported lower respiratory symptoms with a mean age onset of 2.2 ± 2.5 years and only 63/69 (91%) performed specialist assessment at Respiratory Unit. Recurrent pneumonia (33%) and wheezing (31%) were the most reported symptoms. The first respiratory evaluation was performed after surgically correction of gastroesophageal reflux (GER) at mean age of 3.9 ± 4.2 years. Twenty nine patients have undergone to chest CT with contrast enhancement detecting localized atelectasis (41%), residual tracheal diverticulum (34%), bronchiectasis (31%), tracheal vascular compression (21%), tracheomalacia (17%) and esophageal diverticulum (14%). Fifty three patients have undergone to airways endoscopy detecting tracheomalacia (66%), residual tracheal diverticulum (26%), recurrent tracheoesophageal fistula (19%) and vocal cord paralysis (11%). Conclusions Our study confirms that respiratory symptoms often complicate EA and TEF; their persistence despite medical and surgical treatment of GER means that other etiological hypothesis must be examined and that a complete respiratory diagnostic work up must be considered.